Effects of coal oxidation on calorific value - (:unkn) unknown (TAYLOR & FRANCIS INC, 1999)
A brief investigation of the effects of oxidation on the calorific values of three Turkish lignite samples has been made. The lignite sampler have been vacuum dried and oxidized in pure oxygen at 35, 45 and 55 degrees C at 100 kPa for 10 days. The calorific values of the oxidized and unoxidized samples have been measured. A relation has been observed between the extent of oxidation and decrease in calorific value, Various possibilities of modelling the relation have been explored.
Keywords: calorific value; coal oxidation; VICTORIAN BROWN COAL; LOW-TEMPERATURE OXIDATION; OXYGEN